2019
DOI: 10.1039/c8ta11776d
|View full text |Cite
|
Sign up to set email alerts
|

Redox-coupled alkali-metal ion transport mechanism in binder-free films of Prussian blue nanoparticles

Abstract: Our experimental and theoretical studies elucidate the redox-coupled ion transport mechanism and the intrinsic structure–property relationship in binder-free Prussian-blue electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 59 publications
1
40
0
Order By: Relevance
“…Here, we discuss the reason why the proper number of anion vacancies improves the electrochemical performance, especially the kinetics of K + ion insertion/extraction. The anion vacancy might affect the electronic conduction and ionic diffusion of the KMnHCFs as it changes the electronic state and pore sizes [10] . However, we confirmed almost the same electronic conductivity of L‐ and IE‐KMnHCFs, 8.71×10 −7 and 8.36×10 −7 S cm −1 , respectively, and a slightly higher electronic conductivity of 1.63×10 −6 S cm −1 for S‐KMnHCF.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…Here, we discuss the reason why the proper number of anion vacancies improves the electrochemical performance, especially the kinetics of K + ion insertion/extraction. The anion vacancy might affect the electronic conduction and ionic diffusion of the KMnHCFs as it changes the electronic state and pore sizes [10] . However, we confirmed almost the same electronic conductivity of L‐ and IE‐KMnHCFs, 8.71×10 −7 and 8.36×10 −7 S cm −1 , respectively, and a slightly higher electronic conductivity of 1.63×10 −6 S cm −1 for S‐KMnHCF.…”
Section: Resultsmentioning
confidence: 51%
“…Ishizaki et al. suggested that anion vacancies in Fe[Fe(CN) 6 ] y can promote the diffusion of K + ions using cyclic voltammetry data and site energy calculations based on density functional theory (DFT) [10] . They considered that the larger open pores formed in vacancy‐rich Fe[Fe(CN) 6 ] y enhance K + ion diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Since MHCFs have a simple cubic lattice structure like a jungle gym (inset in Fig. 2 ), in which divalent (M 2+ ) and trivalent (M 3+ ) metal cations are cross-linked with each other via cyano-group anion (CN – ), and exhibit many fascinating features 9 11 , they have been extensively investigated from viewpoints of both scientific and industrial aspects 12 18 . Recently, PB (FeHCF) has been applied to remove radioactive cesium-134 ( 134 Cs) and 137 Cs elements from contaminated soils caused by Fukushima nuclear plant accident in 2011 19 23 , because PB has the jungle-gym cubic structure with a 0.5 nm-interstitial site (4 c site in space group) that plays a role in trapping Cs ions efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…1), wherein divalent (M 2+ ) and trivalent (M 3+ ) metal cations are cross-linked with each other via a cyano-group anion (CN À ) and exhibit numerous fascinating features, [10][11][12] they have been extensively investigated from the viewpoints of both scientic and industrial aspects. [13][14][15][16][17][18][19] Recently, PB (FeHCF) was applied for the removal of radioactive cesium-134 ( 134 Cs) and 137 Cs from contaminated soils, which was caused by the Fukushima nuclear plant accident in 2011 (ref. [20][21][22][23][24] because PB has the jungle-gym cubic structure (see Fig.…”
Section: Introductionmentioning
confidence: 99%